Wit's treasury : Renaissance England and the classics - Orgel, Stephen (University of Pennsylvania Press, 2021)
"The title Wit's Treasury alludes to Francis Meres's Palladis Tamia: Wits Treasury; Being the Second Part of Wits Commonwealth, published in 1598. The book has become famous for its early appreciation of Shakespeare, but its relevance to this project is its assumption that the way to praise contemporary English literature was by comparing it with that of Greece and Rome through a "comparative discourse," Elizabethan England is declared part of Palladis Tamia, the treasure house of Pallas Athena. Tamia may also include a pun on the name of the river Thames, so an alternative title would be Athena's Thames. The parallel with the classics was repeatedly invoked in the period, but it was neither simple nor without ambivalence. Wit's Treasury examines that parallel and its complexity"--